2021
DOI: 10.2174/2210303110999201007164919
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Enhancement of Eplerenone using Solvent Melt Method

Abstract: Background: Eplerenone (EPL) is a BCS class II drug, thus, having the poor water solubility. The poor water solubility of this drug leads to the poor dissolution and ultimately shows the poor bioavailability. To overcome this problem, the solid dispersion of EPL was prepared in this study. Methods: This was accomplished by using the solvent melt method as the solid dispersion technique. In this method Pluronic F-68 and F-127 was used as the carrier and different formulations were prepared using the varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Their results reported massive enhancement in EPL bioavailability in vivo, with 1276.26% greater relative bioavailability for the pellet formulation with EPL loaded solid dispersion compared to that of the pellets containing plain EPL 72 . In another study, Agrawal et al 73 succeeded to prepare EPL solid dispersions using a carrier mixture of Pluronic F127 and Pluronic F68 via the solvent melt method. Their results confirmed that the optimized solid dispersion exhibited fast dissolution with almost 98.96% drug dissolved in 30 minutes.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Their results reported massive enhancement in EPL bioavailability in vivo, with 1276.26% greater relative bioavailability for the pellet formulation with EPL loaded solid dispersion compared to that of the pellets containing plain EPL 72 . In another study, Agrawal et al 73 succeeded to prepare EPL solid dispersions using a carrier mixture of Pluronic F127 and Pluronic F68 via the solvent melt method. Their results confirmed that the optimized solid dispersion exhibited fast dissolution with almost 98.96% drug dissolved in 30 minutes.…”
Section: Literature Surveymentioning
confidence: 99%
“…In-situ gel mainly applied for drugs with fast elimination rate (short elimination half-life). EPL was prepared in an oral in situ gel formulation, 74 using different polymers such as sodium alginate, calcium carbonate, sodium citrate, xanthan gum, guar gum and karaya gum. The in situ gel system prepared using guar gum as a polymer was reported to achieve successful sustainment of EPL release.…”
Section: Eplerenone In Solid Dispersionmentioning
confidence: 99%